UTERINE SARCOMA DIAGNOSED AFTER UTERINE ARTERY EMBOLIZATION: A CASE REPORT - Цхай, Виталий Борисович; Гребенникова, Эльвира Константиновна; Домрачева, Марина Яковлевна; Андреева, Алла Андреевна; Бауров, Павел Петрович; Шишигина, Светлана Викторовна (Mother and Baby in Kuzbass, 2023)
Leiomyosarcoma is an extremely aggressive malignant neoplasm associated with an unfavorable overall prognosis for a woman’s life and health. Leiomyosarcoma is mainly a single large formation, located mainly in the myometrium or subserous layer of the uterus. Preoperative diagnosis of sm is difficult, despite the introduction of various diagnostic methods.There are several cases of leiomyosarcoma in which patients with symptomatic uterine fibroids underwent uterine artery embolization. And one of these rare cases is described in this article. A patient with uterine leiomyoma (confirmed histologically) underwent uterine artery embolization, but given the continued growth of the uterine uterus (rapid growth of nodes), the patient was offered a hysterectomy. Histology results revealed leiomyosarcoma.
Keywords: leiomyosarcoma; uterine artery embolization; uterine leiomyoma; symptomatic uterine fibroids; uterine sarcoma